Perception of Healthcare Professionals on the Importance of English Training in Medical Contexts - Sukisno,; Jefriyanto Saud, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
As globalization continues to accelerate, the need for English proficiency among healthcare professionals has become increasingly crucial, especially in the context of international and multicultural healthcare services. This study examines healthcare professionals' perceptions of the importance of English language training in their professional practice in Indonesia. Using a qualitative approach, semi-structured interviews were conducted with 20 healthcare professionals, including doctors, nurses, and administrative staff, working at two international hospitals in Jakarta. The main objective of this study is to understand the need for English language training, the challenges faced in acquiring language proficiency, and recommendations for improving English language training programs tailored to the medical context. The results of the study show that most participants acknowledge the important role of English in enhancing patient care, workplace efficiency, and professional development. The main challenges identified include the lack of specific English for Medical Purposes (EMP) programs, limited time due to busy work schedules, and psychological barriers such as lack of confidence and fear of making mistakes. While general English courses are available, participants highlighted their inadequacy in meeting the specific language demands of the medical field, such as medical terminology, patient interactions, and professional communication. Participants recommended the development of EMP courses tailored to real-world medical scenarios, flexible training schedules, and collaborative learning methods such as role-playing. They emphasized that addressing these gaps in training would not only improve communication skills but also contribute to better healthcare outcomes. This study provides valuable insights into the role of English in the medical field and stresses the need for evidence-based curriculum design that accommodates the unique needs of healthcare professionals. Additionally, the study offers practical recommendations for policymakers, educators, and hospital administrators to enhance the effectiveness of English language training programs in medical institutions